Corporate networks in post-war Britain: Do finance–industry relationships matter for corporate borrowing?. Issue 6 (18th August 2021) - Kern, Philipp; Schnyder, Gerhard
Abstract: The relationship between interlocking directorates and corporate finance patterns is a widely-researched aspect of the literature on national financial systems. This literature often considers the United Kingdom to be analogous to the United States, without directly investigating the nature and impact of finance–industry relationships. Based on a hand-collected data set covering eight benchmark years between 1950 and 2010, the authors start filling this gap by combining historical narratives, social network analysis, and regression analysis. They investigate whether finance–industry relations affect corporate borrowing patterns differently across time periods. The authors find that network-embedding had an impact on corporate borrowing from the 1950s to 1970s, but not thereafter. They also find that network structure and its function do not always evolve in parallel, highlighting limitations of purely structural approaches to understanding the link between corporate networks and firm behaviour and the importance of the historical idiosyncrasies of each country case.